Combined Non-Target Effects of Insecticide and High Temperature on the Parasitoid Bracon nigricans. - Khaled Abbes; Antonio Biondi; Alican Kurtulus; Michele Ricupero; Agatino Russo; Gaetano Siscaro; Brahim Chermiti; Lucia Zappalà (PLoS ONE, 2015)
We studied the acute toxicity and the sublethal effects, on reproduction and host-killing activity, of four widely used insecticides on the generalist parasitoid Bracon nigricans (Hymenoptera: Braconidae), a natural enemy of the invasive tomato pest, Tuta absoluta (Lepidoptera: Gelechiidae). Laboratory bioassays were conducted applying maximum insecticide label rates at three constant temperatures, 25, 35 and 40°C, considered as regular, high and very high, respectively. Data on female survival and offspring production were used to calculate population growth indexes as a measure of population recovery after pesticide exposure. Spinetoram caused 80% mortality at 25°C and 100% at higher temperatures, while spinosad caused 100% mortality under all temperature regimes. Cyantraniliprole was slightly toxic to B. nigricans adults in terms of acute toxicity at the three temperatures, while it did not cause any sublethal effects in egg-laying and host-killing activities. The interaction between the two tested factors (insecticide and temperature) significantly influenced the number of eggs laid by the parasitoid, which was the lowest in the case of females exposed to chlorantraniliprole at 35°C. Furthermore, significantly lower B. nigricans demographic growth indexes were estimated for all the insecticides under all temperature conditions, with the exception of chlorantraniliprole at 25°C. Our findings highlight an interaction between high temperatures and insecticide exposure, which suggests a need for including natural stressors, such as temperature, in pesticide risk assessments procedures.